THE IMPACT OF THE DECISIONS OF THE COURT OF THE EAST AFRICAN COMMUNITY ON THE NATIONAL LEGISLATION OF THE MEMBER STATES OF THE EAST AFRICAN COMMUNITY - R. Shaikhutdinova, Gulnara; U. Vladykina, Anna (Gênero & Direito, 2019)
The subject of this article is the jurisprudence of the Court of the East African Community in cases related to the protection of human rights. The article examines in detail the jurisprudence, which, to some degree, influenced changes in legislation in some member states of the East African Community, and in some cases prevented further violations of human rights. The authors also raise the issue of the lack of jurisdiction of the East African Court to consider complaints related to human rights violations. The authors pay particular attention to the human rights situation in Burundi, Kenya, Rwanda, and Uganda, which has developed since the Court has passed decisions. The authors also raise the issue of the place and importance of the Court of the East African Community in the regional system of human rights protection in Africa, highlight the positive contribution of the Court to the human rights situation in the subregion. The article demonstrates the existence of complex, controversial problems, the further functioning of the court of the East African Community as a quasi-judicial body for the protection of human rights depends on the need to solve it. The solution to these problems depends to a large extent on whether member states can agree to sign a protocol that gives the Court jurisdiction to handle complaints related to human rights violations in the subregion